THE EFFECTIVENESS OF COOPERATIVE LEARNING IN ENGLISH LANGUAGE CLASSROOMS - Lolakhon Nazarova (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Cooperative learning has gained significant attention as an effective instructional approach in English language classrooms. This study examines the impact of cooperative learning strategies on students’ language proficiency, motivation, and classroom interaction. Drawing on existing empirical research and theoretical frameworks, the article highlights how cooperative learning enhances communicative competence, fosters learner autonomy, and improves academic achievement in English as a Foreign Language (EFL) contexts. The findings suggest that cooperative learning, when properly implemented, contributes positively to both linguistic and social outcomes in English language education.